Digitalization of immunization programmes in Europe: results from the EUVIS project. (30th September 2020) - Odone, A; Gianfredi, V; Frascella, B; Balzarini, F; Oradini Alacreu, A; Signorelli, C
Abstract: The second and final phase of the EUVIS (EUrope Vaccines ICT Strategies) project, coordinated by the School of Public Health of the University Vita-Salute San Raffaele in Milan (Italy), aims at collecting best practices on the use and impact of Information and Communication Technologies (ICT) and digital tools to increase vaccine uptake and ultimately vaccination coverage in Europe. The field of ICT has flourished in recent years revolutionizing the processes of gathering, spreading and utilizing health information among healthcare providers, citizens and mass media. In particular, we are interested in any digital technology that can improve vaccine uptake supporting actions aimed at both increasing the demand of vaccines (i.e provide access to information through telecommunications, networks, the Internet, wireless, mobile devices), and the supply of effective and efficient life-course immunization services (i.e ICT-based interventions to support immunization programmes delivery and their monitoring). Within EUVIS we have previously conducted a series of systematic reviews to pool available evidence from experimental studies on the impact of selected ICT-based intervention (i.e. e-mail reminders, personal health records, among others) to improve vaccine uptake and other associated outcomes. In the current study, second and final phase of the EUVIS project, we are conducting a survey at the European level to gather original data on the use and impact of ICT and digital tools within immunization programmes in selected countries. The survey tool was developed on the basis of findings from EUVIS phase one and experts' consultation; it consisted on a 55-item questionnaire, distributed to public health professionals working in health agencies, institutions and the academia to build "ICT and immunization" countries' profile, as well as to gather, pool and critically appraise data on perceived potential and challenges of immunization programmes' digitalization in Europe.